Rupture or Continuity? Revisiting the Basic Themes of the Historiography of the 21 April Dictatorship - Kouki, Eleni (Historein, 2021)
What did the 1967–1974 dictatorship represent for Greece? A violent and illegal episode, a mere parenthesis in the course of its parliamentary history, or an event with deep roots in Greek society and politics? These two basic, albeit contradictory views require us to consider how the last dictatorship in Greece was conceived in public and academic discourse as well as how these two discourses interacted. The main argument of this article is that even the most self-evident concepts about the character of the 1967 dictatorship, so trivial that we hardly perceive them as concepts, emerged through complex cultural processes. More specifically, it examines a series of well-known academic texts or texts produced in academic settings, dating from the junta era to the late 1980s. Although the research on the dictatorship has progressed greatly since then, this article seeks to show that in the first two decades after its collapse, there was a rich production of perceptions regarding the dictatorship that continue to shape our understanding of the period, which is why it is essential to reflect on them.